Assessment of tacrolimus and creatinine concentration collected using Mitra microsampling devices. (September 2020) - Marshall, David J; Kim, Jon Jin; Brand, Sarah; Bryne, Catherine; Keevil, Brian G
Background: Current practice requires regular venous blood samples for monitoring of tacrolimus concentrations post renal transplant requiring regular hospital visits. Mitra devices use volumetric absorptive microsampling technology and absorb a fixed amount of blood (10 μ L) from a capillary blood sample. They are a viable volumetric alternative to dried blood spots and are able to be posted to the laboratory for analysis. Objective: The aim was to develop and validate liquid chromatography-tandem mass spectrometry (LC-MS/MS) assays for tacrolimus and creatinine analysis using Mitra devices. The usefulness of this approach was assessed in renal transplant patients routinely monitored for tacrolimus and creatinine. Method: Routine tacrolimus samples were used to assess the utility and reliability of Mitra sampling. Shared sample preparation for both tacrolimus and creatinine was carried out in a 96-deep well plate; mass spectrometric analysis was then undertaken for tacrolimus followed by re-injection for creatinine analysis. Results: Comparison of 131 Mitra samples with a routine LC-MS/MS assay for tacrolimus showed a minimal bias –5.6% (95% CI –8.5 to –2.7%). Comparison of 135 serum and Mitra samples for creatinine using a fully validated LC-MS/MS assay showed a bias –6.5% (95% CI –8.5 to –4.5%). Discussion: We have developed assays for tacrolimus and creatinine on fingerprick blood using the Mitra device and believe this approach provides a viable alternative to repeated venepuncture for therapeutic drug monitoring. This method could open up the opportunity for patients to perform tacrolimus and kidney function monitoring at home.